Bridging Therapy Versus Direct Mechanical Thrombectomy in Patients with Acute Ischemic Stroke due to Middle Cerebral Artery Occlusion: A Clinical- Histological Analysis of Retrieved Thrombi. Issue 6 (June 2019) - Gong, Li; Zheng, Xiaoran; Feng, Lijin; Zhang, Xiang; Dong, Qiong; Zhou, Xiaoyu; Wang, Haichao; Zhang, Xiaojun; Shu, Zhongwen; Zhao, Yanxin; Liu, Xueyuan
Mechanical thrombectomy (MT) is effective in managing patients with acute ischemic stroke (AIS) caused by large-vessel occlusions and allows for valuable histological analysis of thrombi. However, whether bridging therapy (pretreatment with intravenous thrombolysis before MT) provides additional benefits in patients with middle cerebral artery (MCA) occlusion remains unclear. Therefore, this study aimed to compare the effects of direct MT and bridging therapy, and to elucidate the correlation between thrombus composition and stroke subtypes. Seventy-three patients with acute ischemic stroke who received MT, were eligible for intravenous thrombolysis, and had MCA occlusion were included. We matched 21 direct MT patients with 21 bridging therapy patients using propensity score matching and compared their 3rd-month clinical outcomes. All MCA thrombi (n = 45) were histologically analyzed, and the red blood cell (RBC) and fibrin percentages were quantified. We compared the clot composition according to stroke etiology (large-artery atherosclerosis and cardioembolism) and intravenous thrombolysis application. The baseline characteristics showed no difference between groups except for a higher atrial fibrillation rate and NIHSS score on admission in the direct MT group. We performed a supportive analysis using propensity score matching but could not find any differences in the functional outcome, mortality, and intracerebral hemorrhage. In the histological clot analysis, the cardioembolic clots without intravenous thrombolysis pretreatment had higher RBC (P = 0.042) and lower fibrin (P = 0.042) percentages than the large-artery atherosclerosis thrombi. Similar findings were observed in the thrombi treated with recombinant tissue plasminogen activator (P = 0.012). In conclusion, there was no difference in the functional outcomes between the direct MT and bridging therapy groups. However, randomized trials are needed to elucidate the high ratio of cardioembolism subtype in our group of patients. The histological MCA thrombus composition differed between cardioembolism and large-artery atherosclerosis, and this finding provides valuable information on the underlying pathogenesis and thrombus origin.